Analisis Strategi Promosi pada Usaha Percetakan dan Reklame Garuda Printing di Kota Gunungsitoli (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the promotional strategies implemented by Garuda Printing, a business engaged in the printing and advertising industry in the city of Gunungsitoli. The background of this research is based on the still low effectiveness of Garuda Printing's promotional efforts, which until now have relied on conventional methods such as distributing brochures, installing banners, and word-of-mouth marketing. Meanwhile, technological advancements and the rise of digital media have transformed promotional patterns into more modern and interactive forms. This research employs a descriptive qualitative approach with data collection techniques including interviews, direct observation, and documentation. The findings indicate that the promotional strategies employed remain basic and uncoordinated, primarily due to the absence of a dedicated unit or division responsible for marketing. Internal challenges include the limited number of human resources skilled in digital marketing and budget constraints for promotional activities. Externally, the business faces intense competition from similar companies and shifting consumer preferences towards digital-based services. Based on these findings, it is concluded that Garuda Printing needs to update its promotional strategies in a structured and adaptive manner, particularly by leveraging digital media, in order to enhance competitiveness and expand market reach in today's digital era.